PENALAKSANAAN SINDROMA RENJATAN DENGUE DENGAN EDEMA PARU - Somia, Agus; Parwati, Tuti (journal of internal medicine, 2010)
Dengue Hemorrhagic Fever (DHF) is a systemic disease caused by one of the four types Dengue Viruses. DHF transmittedby a mosquito called Aedes aegyptii. Clinical spectrums of dengue infection widely vary from asymptomatic, undifferentiatedfever, dengue fever, dengue hemorrhagic fever, and dengue shock syndrome grade III and IV. Dengue infections remain on thetop list of infectious disease found in our country and several South-East Asia Nations. Pathognomonic clue differing denguehemorrhagic fever with dengue fever is the presence of plasma leakage due to the increasing of vascular permeability. Dengueshock syndrome is a medical emergency needing direct and correct ß uid resuscitation to deal with hemodynamic disturbance andplasma leakages without causing ß uid overload or further complication. We report an 18 years old male with chief complain offever for 6 days and newly lung edema after 12 hours of admission. Patient diagnosed with 3rd grade of dengue hemorrhagic feverwith lung edema. Patient then undergone ß uid resuscitation with crystalloid and colloid ß uid and given furosemide as diureticagent simultaneously. Finally getting better after Þ ve days of treatment in hospital